Social effect of implementing active longevity strategies - V. I. Aleshnikova; T. A. Burtseva; Z. A. Nuriddinov (Управление)
The article analyses the domestic and foreign practices of making decisions on financing projects related to demography, health, and social protection of the population. The paper considers declarations, concepts, and strategies directing to solve the problem of population aging, which is relevant for countries of the Europe, North America, the Russian Federation. The authors investigate the issues of an assessment of the social effect of implementing strategies and programs for active longevity, in domestic science and practice and conclude, that at present, universal methodology is not developed, and the existing standard approaches are adapted from the management of corporate structures. The purpose of the article is to test the system of measuring the social effect of implementing the concept of active longevity in the region. The methodological basis of the study are the factor approach, methods of analysis of time series, the factor approach, as well as recommendations of the World Health Organization (WHO), the United Nations Organization (UN) and the European Union (EU). The scientific novelty of the presented results lies in the author`s methodological developments: the interpretation of the social effect of the active longevity strategy and the system of statistical indicators for assessing the social effect in the implementation of active longevity strategies in the region. The practical significance of the results is that the regions of the Russian Federation can use the author’s system of social effect meters to monitor strategies and programs for the implementation of active longevity. The use of the system of indicators will provide a solution to the problem of its quantitative assessment, it will allow us to find out the shortcomings of regional target indicators at the planning stage and will help to increase the level of consistency of the goals of regional strategies with national goals and requirements of international organizations.